Angiotensin-(1-7) and Alamandine Promote Anti-inflammatory Response in Macrophages In Vitro and In Vivo. (21st February 2019) - de Carvalho Santuchi, Melissa; Dutra, Miriane Fernandes; Vago, Juliana Priscila; Lima, Kátia Maciel; Galvão, Izabela; de Souza-Neto, Fernando Pedro; Morais e Silva, Mario; Oliveira, Aline Cristina; de Oliveira, Flávia Carvalho Bittencourt; Gonçalves, Ricardo; Teixeira, Mauro Martins; Sousa, Lirlândia Pires; et al.
Abstract : The renin-angiotensin system (RAS) peptides play an important role in inflammation. Resolution of inflammation contributes to restore tissue homeostasis, and it is characterized by neutrophil apoptosis and their subsequent removal by macrophages, which are remarkable plastic cells involved in the pathophysiology of diverse inflammatory diseases. However, the effects of RAS peptides on different macrophage phenotypes are still emerging. Here, we evaluated the effects of angiotensin-(1-7) (Ang-(1-7)) and the most novel RAS peptide, alamandine, on resting (M0), proinflammatory M(LPS+IFN- γ ), and anti-inflammatory M(IL-4) macrophage phenotypes in vitro, as well as on specific immune cell populations and macrophage subsets into the pleural cavity of LPS-induced pleurisy in mice. Our results showed that Ang-(1-7) and alamandine, through Mas and MrgD receptors, respectively, do not affect M0 macrophages but reduce the proinflammatory TNF- α, CCL2, and IL-1 β transcript expression levels in LPS+IFN- γ -stimulated macrophages. Therapeutic administration of these peptides in LPS-induced inflammation in mice decreased the number of neutrophils and M1 (F4/80 low Gr1 + CD11b med ) macrophage frequency without affecting the other investigated macrophage subsets. Our data suggested that both Ang-(1-7) and alamandine, through their respective receptors Mas and MrgD, promote an anti-inflammatory reprogramming of M(LPS+IFN- γ )/M1 macrophages under inflammatory circumstances and potentiate the reprogramming induced by IL-4. In conclusion, our work sheds light on the emerging proresolving properties of Ang-(1-7) and alamandine, opening new avenues for the treatment of inflammatory diseases.